2007
DOI: 10.1080/10236190701458857
|View full text |Cite
|
Sign up to set email alerts
|

Maximal regularity of discrete second order Cauchy problems in Banach spaces

Abstract: Abstract. We characterize the discrete maximal regularity for second order difference equations by means of spectral and R-boundedness properties of the resolvent set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In Ref. [28], the authors used a Fourier multiplier theorem, due to Blunck (see Ref. [13], Theorem 1.3), to study maximal regularity of equation (1.2) in the border case r ¼ 1.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [28], the authors used a Fourier multiplier theorem, due to Blunck (see Ref. [13], Theorem 1.3), to study maximal regularity of equation (1.2) in the border case r ¼ 1.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the authors investigated maximal regularity in discrete Hölder spaces for the Crank-Nicolson scheme. In [18] maximal regularity for linear parabolic difference equations is treated, whereas in [13] a characterization in terms of R-boundedness properties of the resolvent operator for linear second order difference equations was given. See also the recent paper by Kalton and Portal [21], where they discussed maximal regularity of power-bounded operators and relate the discrete to the continuous time problem for analytic semigroups.…”
Section: Introductionmentioning
confidence: 99%
“…A motivation for our studies in this paper stems in the recent article by Arendt and Bu [4] and Cuevas and Lizama [19]. In the first one the authors consider the operator-valued Marcinkiewich multiplier theorem and maximal regularity, and the second one the authors shown a characterization for the maximal regularity for a second order difference equation by R-boundedness properties of the resolvent operator which defines the equation.…”
Section: Introductionmentioning
confidence: 99%
“…The sequences of linear and bounded operators C(n) and S(n) were introduced in [19] to represent the solution of (2.2) in the border case r = 1. …”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation